2022
DOI: 10.3389/fcvm.2022.813085
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Machine Learning-Based Radiomics Model on Cardiac Computed Tomography of Epicardial Adipose Tissue in Predicting Characteristics and Recurrence of Atrial Fibrillation

Abstract: PurposeThis study aimed to evaluate the feasibility of differentiating the atrial fibrillation (AF) subtype and preliminary explore the prognostic value of AF recurrence after ablation using radiomics models based on epicardial adipose tissue around the left atrium (LA-EAT) of cardiac CT images.MethodThe cardiac CT images of 314 patients were collected wherein 251 and 63 cases were randomly enrolled in the training and validation cohorts, respectively. Mutual information and the random forest algorithm were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Epicardial adipose tissue is a special visceral adipose tissue located between the myocardium and the visceral pericardium ( 14 ). This privileged location positions EAT to exert important paracrine and vasocrine effects on neighboring cardiomyocytes ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Epicardial adipose tissue is a special visceral adipose tissue located between the myocardium and the visceral pericardium ( 14 ). This privileged location positions EAT to exert important paracrine and vasocrine effects on neighboring cardiomyocytes ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics quantitatively assesses tissue heterogeneity, which is an objective measure but not visually recognizable, by reflecting the distribution of gray level values and spatial arrangement of the pixels ( 34 ). Radiomics analysis of EAT has been previously shown to be useful in identifying AF ( 23 , 24 ), differentiating AF characteristics, and predicting AF recurrence ( 14 ). These studies revealed that radiomics analysis of EAT may have the potential to provide an accurate prediction for POAF after PEA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, ML algorithms are appropriate for processing highdimensionality data, given reasonable optimization [7]. Classi cation models based on ML, deep learning (DL) or radiomic methods to predict the outcome of AF have been reported in numerous studies [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%